A metal-free electrochemically exfoliated graphene/graphitic carbon nitride nanocomposite for CO2 photoreduction to methane under visible light irradiation. Issue 1 (February 2023) - Alshamkhani, Maher T.; Putri, Lutfi Kurnianditia; Lahijani, Pooya; Lee, Keat Teong; Mohamed, Abdul Rahman
Abstract: In this work, an electrochemically exfoliated graphene/graphite carbon nitride ((EG)/g-C3 N4 ) heterojunction photocatalyst was synthesized for CO2 photoreduction to methane. Different photocatalyst samples with various EG loadings were prepared by the impregnation-calcination method, and their photoreduction performances were tested in a continuous-flow CO2 photoreactor under visible light irradiation. Results indicated that the best-performing photocatalyst (0.075 EG-CN) revealed the highest CH4 evolution of 21.32 μmol gcatalyst −1 after 6 h of light irradiation that manifested a significant 7.25-fold enhancement in CH4 production compared to the pure CN with 98.6% selectivity for CH4 production. The developed photocatalyst was extensively analyzed using SEM, TEM, XRD, FTIR, BET and XPS characterizations, and the relationship between the physicochemical properties of the photocatalyst and its CO2 photoreduction performance was extensively discussed. The PL, TPR, and UV-Vis tests showed that introducing the EG into the photocatalyst enhanced the visible light absorptions and facilitated the fast transfer and separation of photogenerated electron-hole. The mechanism of visible-light photoreduction of CO2 to CH4 with EG-CN nanocomposite was also proposed and discussed. The optimum photocatalyst possessed high stability after four consecutive cycles of CO2 photoreduction to CH4 at ambient conditions without any significant change in the CH4 production. Graphical Abstract: ga1 Highlights: Scalable fabrication of electrochemically exfoliated graphene (EG)-g-C3 N4 for CO2 photoreduction to CH4 . Lowering the g-C3 N4 bandgap from 2.65 to 2.36 eV after loading of EG in the photocatalyst. Optimum loading of graphene suppressed the direct and fast charge recombination. A CH4 selectivity of 98.62% achieved using 0.075 EG-CN composite after 6 h of light irradiation.